Pengembangan Strategi Bisnis Ekowisata Yang Berkelanjutan - Devi Roza K. Kausar; Reny Andriyanty; Haswan Yunaz (Journal of Environmental Engineering and Waste Management, 2020)
This research was conducted to combine the potential ecological conditions with the business model of Taman Nasional Gunung Gede Pangrango (TNGGP). Objectives: The goal of this research is to recomend the ecotourism bussiness strategy that combines with principles of sustainable development in the TNGGP.  The research design was descriptive and analyzed by SWOT analysis. The recomended business strategies are strictly guardhouse supervision, for climbers are not allowed to cut, burn, move ar damage the natural beauty of TNGGP enviroment, vandalism and littering prohibited, camp in predetermined place and oriented  the visitor how do ecotourism properly and correctly. The strategy can be applied with maximize the efforts to prevent the natural ecology and aesthetics damage,  reduce water pollution around TNGGP, improve visitor behavior and their awareness not to damage the TNGGP area,  enhance the role of communities around TNGGP in order to improve community welfare.